2008
DOI: 10.1159/000128567
|View full text |Cite
|
Sign up to set email alerts
|

<i>DNAI1</i> Mutations Explain Only 2% of Primary Ciliary Dykinesia

Abstract: Background: Primary ciliary dyskinesia (PCD) is a rare recessive hereditary disorder characterized by dysmotility to immotility of ciliated and flagellated structures. Its main symptoms are respiratory, caused by defective ciliary beating in the epithelium of the upper airways (nose, bronchi and paranasal sinuses). Impairing the drainage of inhaled microorganisms and particles leads to recurrent infections and pulmonary complications. To date, 5 genes encoding 3 dynein protein arm subunits (DNAI1, DNAH5 and DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 43 publications
3
44
0
Order By: Relevance
“…The causal mutation in >50% of PCD cases remains unknown. Of the known causes, DNAI1 (2%) and DNAH5 (15%) constitute the largest proportions (4,(20)(21)(22). In all of the above cases, sperm structure at a light-microscopic level appears normal, but EM studies revealed only axonemal defects; in contrast, it is important to note that the dynein arms, nexin linkages and radial spokes were normal in this man and that the different defects in sperm structure suggested that studies of the above genes were unlikely to be valuable.…”
Section: Discussionmentioning
confidence: 99%
“…The causal mutation in >50% of PCD cases remains unknown. Of the known causes, DNAI1 (2%) and DNAH5 (15%) constitute the largest proportions (4,(20)(21)(22). In all of the above cases, sperm structure at a light-microscopic level appears normal, but EM studies revealed only axonemal defects; in contrast, it is important to note that the dynein arms, nexin linkages and radial spokes were normal in this man and that the different defects in sperm structure suggested that studies of the above genes were unlikely to be valuable.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory cilia were either immotile or showed some residual flickery movement. [17,[37][38][39][40]. This gene was identified based on a candidate gene approach since Chlamydomonas algae lacking IC78 lost 70% of their motility and were slow swimming [17,41].…”
Section: Dnah5mentioning
confidence: 99%
“…Genetic testing holds promise as a diagnostic approach in patients with a clinical phenotype compatible with PCD, as approximately 50% of PCD can be accounted for by biallelic mutations in 12 genes 5–23. Mutations in two genes; dynein axonemal intermediate chain 1 ( DNAI1 ), and dynein axonemal heavy chain 5 ( DNAH5 ), that code for ciliary outer dynein arm (ODA) proteins are the most common genetic causes of PCD (18–30% of PCD),9 10 13 14 and mutations in the remaining genes are relatively uncommon.…”
Section: Introductionmentioning
confidence: 99%